“Conselho de amigo, aviso do céu”: contributos para a análise semântico-pragmática dos atos ilocutórios de conselho e de aviso em confronto com o de ameaça - de Almeida Carla Aurélia (Revista da Associação Portuguesa de Linguística, 2016)
Based on selected examples of spoken European Portuguese, this paper discusses the organization and functioning of the illocutionary acts of advice and warning, highlighting the resemblances and differences between them and discourse acts such as threats and promises, hypothetic warnings and conditional threats. After the analysis of Grice’s notion of “meaning” and Austin’s notion of “uptake”, we emphasize the relation between intention and convention, in the analysis of Searle’s illocutionary acts, and map the rules that determine illocutionary force indicating devices. The interpretation of illocutionary values in the sequence of interventions highlights the relation between discursive practices and face work theory.